2008
DOI: 10.1177/1063426608321690
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Linking Maternal Depressed Mood to Growth in Adolescent Substance Use

Abstract: Maternal depression has been implicated in the development of adolescent substance use. Conceptualizing depression as a continuum, the aims of this study were to (a) understand the relationship between maternal depressed mood and risk factors associated with adolescent substance use; (b) understand the relationship between maternal depressed mood and level and growth in adolescent alcohol, cigarette, and marijuana use assessed at multiple time points during adolescence; and (c) examine the unique and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Finally, we did not have data on parental cannabis use or young adult depressive symptoms, which have been shown in some studies to affect cannabis use in offspring of parents affected by divorce or depression (Cortes et al, 2009;Hayatbakhsh et al, 2006). However, we controlled for parental cigarette smoking, which may be a proxy indicator of parental substance dependence (Degenhardt et al, 2001;Martinez-Ortega et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, we did not have data on parental cannabis use or young adult depressive symptoms, which have been shown in some studies to affect cannabis use in offspring of parents affected by divorce or depression (Cortes et al, 2009;Hayatbakhsh et al, 2006). However, we controlled for parental cigarette smoking, which may be a proxy indicator of parental substance dependence (Degenhardt et al, 2001;Martinez-Ortega et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This compounded stress may contribute to the use of illegal drugs as a coping mechanism during the adolescent years of the young adults in our study (the average age of parental divorce was 17 years), which then have effects on substance use that extend into adulthood (Fawzy et al, 1983;Needle et al, 1990;Regan and Beaver, 2010). A study of non-clinical depression in mothers showed that it impacted adolescent offsprings' initiation of cannabis use (Cortes et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations